Received and Perceived Status of Health Management Information System (HMIS) Software: A Structural Equation Model (SEM) Approach (Medico Legal Update, 2021)
More thansupply the demand for health care usually determines the design of public health services. This ismore so when technological developments, including that of information and communication technologies,pierce through the process of utilization of any service by the public. Although prior research papers havefocused on the factors that impact on the adoptionof information technology, there are limited empiricalresearch works that simultaneouslycapture technology factors (TAM, TAM2) and end-user developmentspecific factors (perceived technology usage and intention to recommend) helping healthcare professionalsto adopt Health Management Information System (HMIS) software in the healthcare environment. To fill thisgap, the present paper used the Technology Acceptance Model (TAM), the extended TAM model (TAM2)and identified the important determinants of user acceptance perceived risk and trust. This is specificallyundertaken in order to describe ESIChealthcare professionals behavioral intention to adopt HMIS softwareservices. The study was conducted in the Employees’ State Insurance Corporation (ESIC) main hospitaland dispensaries in the Tirunelveli sub-region. The required data were collected from 171 ESIC healthcareprofessionals in the Tirunelveli sub-region. AStructural Equation Model (SEM) approach was used.Convergence anddivergence with earlier findings were found, confirming that Perceived Usefulness (PU),Perceived Ease of Use (PEOU), social influence, facilitating conditions and training hadsignificant influenceon the intention of healthcare professionals to adopt HMIS software. The study provideda basis for furtherrefinement of technology adoption model.Improvingperceived usefulness factor (perceived long-termusefulness) may turn healthcare professionals towards adoption of HMIS